2016
DOI: 10.1016/j.idairyj.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and immunomodulatory activity of transglutaminase-treated sodium caseinate hydrolysates

Abstract: Original citationCermeño This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Findings from previous studies suggest that the comet assay may be the most sensitive assay to determine antioxidant activity in cells. Cermeño et al () reported that casein hydrolysates failed to significantly restore GSH concentrations in H 2 O 2 ‐challenged U937 cells. However, in the same study one of the casein hydrolysates showed protective effects against H 2 O 2 ‐induced DNA damage in U937 cells as assessed using the comet assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from previous studies suggest that the comet assay may be the most sensitive assay to determine antioxidant activity in cells. Cermeño et al () reported that casein hydrolysates failed to significantly restore GSH concentrations in H 2 O 2 ‐challenged U937 cells. However, in the same study one of the casein hydrolysates showed protective effects against H 2 O 2 ‐induced DNA damage in U937 cells as assessed using the comet assay.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from previous studies suggest that the comet assay may be the most sensitive assay to determine antioxidant activity in cells. Cermeño et al (2016) (Ichikawa et al, 2010). Previous studies have reported that enzymatic hydrolysis of collagen or gelatin using two or more proteases in combination may generate hydrolysates with greater antioxidant activity compared to single proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that the activity of NF-κβ, one of the major inflammatory signalling pathways, may be reduced in cells exposed to casein hydrolysates (Altmann et al, 2016;Malinowski, Klempt, Clawin-Rädecker, Lorenzen, & Meisel, 2014). The hydrolysis of casein using mammalian, bacterial or plant derived enzymes has also been reported to have immunomodulating effects on Jurkat T cells in other studies (Cermeño et al, 2016;Lahart et al, 2011;Phelan et al, 2009). To the best of our knowledge, no study has compared the cellular antioxidant and anti-inflammatory activities of sodium caseinate hydrolysates generated under the same conditions [hydrolysis time and enzyme:substrate (E:S) ratio], using a range of proteolytic preparations.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…4 More recently, the hydrolysis of casein using Prolyve®, generated a hydrolysate which prevented H 2 O 2 -induced DNA damage in U937 cells (Cermeño, FitzGerald, & O'Brien, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The antioxidant activity of the non-conjugated and conjugated samples was determined using the ORAC assay following the method described by Cermeño, FitzGerald, and O'Brien (2016).…”
Section: Extent Of Conjugationmentioning
confidence: 99%